The circHMGCS1-miR-205–5p-ErBB3 axis mediated the Sanggenon C-induced anti-proliferation effects on human prostate cancer. (January 2023) - Li, Jie; Cao, Xinyue; Chu, Ting; Lin, Kehao; Chen, Lei; Lv, Junlin; Tan, Yujun; Chen, Miaomiao; Li, Minjing; Wang, Kejun; Zheng, Qiusheng; Li, Defang
Abstract: Prostate cancer (PCa) is associated with a high incidence and metastasis rate globally, resulting in an unsatisfactory prognosis and a huge economic burden due to the current deficient of therapeutic strategies. As the most abundant component of Cortex Mori, Sanggenon C (SC) is well known to possess bioactivities in tumors, but its mechanism is poorly understood. Consequently, we attempted to investigate whether SC could modulate circular RNA(s) levels and hence anti-PCa development. We found that SC dramatically promoted cell apoptosis and induced G0/G1 phase arrest in PCa cell lines via the circHMGCS1-miR-205–5p-ErBB3 axis. In brief, circHMGCS1 is highly expressed in PCa and is positively correlated with the degree of malignancy. Over-expression of circHMGCS1 is not only associated with the proliferation of PCa cells but also blocks SC-induced pro-apoptotic effects. As a verified sponge of circHMGCS1, miR-205–5p is down-regulated in PCa tumors, which negatively regulates PCa cell proliferation by modulating ErBB3 expression. After miR-205–5p mimics or inhibitors were used to transfect PCa cells, the effects of circHMGCS1 OE and SC on PCa cells were completely diminished. Similar to miR-205–5p inhibitors, siErBB3 could oppose SC-triggered pro-apoptotic effects on PCa cells. All these results were confirmed in vivo . Together, SC exerts its anti-tumor effects on PCa by inhibiting circHMGCS1 expression and results in the latter losing the ability to sponge miR-205–5p. Subsequently, unfettered miR-205–5p could mostly down-regulate ErBB3 expression by binding to the 5′UTR of ErBB3 mRNA, which eventually resulted in PCa cell cycle arrest and pro-apoptosis. Graphical Abstract: A schematic map showing the antitumor mechanisms of SC on PCa through the circHMGCS1-miR205–5p-ErBB3 axis. SC exerts its anti-tumor effects on PCa by inhibiting circHMGCS1 expression and results in the loss of the ability to sponge miR-205–5p. Subsequently, unfettered miR-205–5p could mostly down-regulate ErBB3 expression by binding to the 5′UTR of ErBB3 mRNA, which further activated the PI3K/AKT pathway and eventually resulted in PCa cell cycle arrest and pro-apoptosis. ga1 Highlights: High expressed circHMGCS1 obviously promotes prostate cells proliferation by acting as a sponge of miR-205–5p. As potential target of miR-205–5p, ErbB3 with highly expressed in prostate cancer induces Pca cell proliferation via activate PI3K-AKT pathway. Sanggenon C (SC) induces prostate cancer cells G0/G1 phase arrest and apoptosis by regulating circHMGCS1/miR-205–5p/ErbB3 axis.